Composting plants as a technology for the transformation of agro-industrial residue into organic fertilizer - Feitosa, Bruno Fonsêca; Alcântara, Charlene Maria de; Oliveira Neto, Juvêncio Olegário de; Silva, Álvaro Gustavo Ferreira da; Oliveira, Emanuel Neto Alves de; Albuquerque, Walker Gomes de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
The increase in the consumption of ready-to-eat foods has also increased the generation of agro-industrial waste. The organic matter present in these residues causes damage to the environment when they are improperly disposed of. Composting is a technology that uses these residues to obtain a sustainable material that can be used as a biofertilizer, without harming the environment. The objective was to collect and analyze data related to composting as a technology capable of transforming agro-industrial waste into organic fertilizer. For this, keywords were defined and a survey of information in the SciELO database was carried out. The keyword [composting AND (“agro-industrial waste” OR “agro-industrial waste”)], in English, obtained the best representation and refinement. Annual evolution data were observed between 2007 and 2020, with the number of publications fluctuating over the period. Considering the 13 selected scientific articles, a total of 4 countries were highlighted as the headquarters of the research executing institutions, namely: Brazil, Chile, Mexico and Portugal. The thematic area “Agrarian Sciences” and the journal “Engenharia Agrícola” have the largest number of publications in their respective groups. There was no relationship between the number of publications of scientific articles and the impact factor presented by the journal. The relevance of the control of humidity, aeration, temperature, pH, carbon and nitrogen ratio (C:N) and granulometry was verified. Therefore, composting is a potential technology to transform agro-industrial waste into organic fertilizer.